Mehran vs. Mehran2 pre-procedure: which score better predicts risk of contrast-induced acute kidney injury in patients with acute coronary syndrome? - Matheus Santos Moitinho; Dulce Barbosa; Attilio Galhardo; Adriano Caixeta; Eduesley Santana-Santos; Maximina Cunha; Beatriz Santana Prado; Cassiane Dezoti da Fonseca (PeerJ)
Background Contrast-induced acute kidney injury (CI-AKI) is a significant concern during percutaneous coronary intervention (PCI) procedures. The novel Mehran 2 pre-procedural risk score, an updated version of the original Mehran score, shows promise as a predictive tool. However, its effectiveness specifically in acute coronary syndrome (ACS) patients requires further investigation. This study aims to evaluate the performance of Mehran 2 pre-procedure risk score compared to original score in predicting CI-AKI risk in acute coronary syndrome patients undergoing PCI. Material and Methods A prospective cohort study was conducted with patients with ACS undergoing PCI, who were followed up for 90 days (December 2019–February 2021). The Mehran 2 CI-AKI risk score with pre-procedure data was compared with the original Mehran score. Receiver operating characteristic (ROC) curve and area under the ROC curve (AUC-ROC) were used to evaluate the discriminative capacity. Results 192 patients were analyzed and 33% (n = 64) developed CI-AKI. CI-AKI outcome was associated with advanced age, arterial hypertension, chronic kidney disease, troponin T, hemodynamic instability, serum hemoglobin, serum creatinine, and higher both Mehran scores. Both scores demonstrated good agreement. The original Mehran score demonstrated superior CI-AKI stratification with higher sensitivity (85.94%) and specificity (60.16%) compared to the Mehran 2 pre-procedural score (sensitivity 50%, specificity 75%). Significant differences were observed in the discriminative performance between both scores. Conclusion Sociodemographic, clinical, and laboratory variables were associated with CI-AKI. The original Mehran score demonstrated more consistent discriminative capacity for predicting CI-AKI risk in ACS patients undergoing PCI compared to the Mehran 2 pre-procedural score.